Negotiations between the Greek and the Turkish president under the auspices of the United Nations. F.l.t.r. Clerides, Munoz and Denktaşh
Negotiations between the Greek and the Turkish president under the auspices of the United Nations. F.l.t.r. Clerides, Munoz and Denktaşh.